2018
DOI: 10.1111/1365-2664.13307
|View full text |Cite
|
Sign up to set email alerts
|

Cover crops in arable lands increase functional complementarity and redundancy of bacterial communities

Abstract: Reducing the deleterious effects of intensive tillage and fertilization on ecosystem integrity and human health is challenging for sustainable agriculture. The use of cover crops has been advocated as a suitable technique for this purpose, but scientific evidence to support this has been scarce. After four years and a complete rotation, including wheat, maize, and green pea as main crops in a ploughing system, we investigated the respective and combined effects of cover crops and nitrogen fertilization on soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 85 publications
2
26
0
Order By: Relevance
“…These sensitive taxa may serve as useful indicators for probing the complex microbial behaviors, or even as bioindicators of soil health [26]. Studies on responsive taxa have thus far shown that CC and tillage primarily impose selection pressures on the soil microbes by changing the soil nutrient availability and quality [30,34,35]. Due to the novelty of metagenomics studies in agricultural research, field studies searching for indicator taxa within systems deploying cover cropping and tillage are still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These sensitive taxa may serve as useful indicators for probing the complex microbial behaviors, or even as bioindicators of soil health [26]. Studies on responsive taxa have thus far shown that CC and tillage primarily impose selection pressures on the soil microbes by changing the soil nutrient availability and quality [30,34,35]. Due to the novelty of metagenomics studies in agricultural research, field studies searching for indicator taxa within systems deploying cover cropping and tillage are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the novelty of metagenomics studies in agricultural research, field studies searching for indicator taxa within systems deploying cover cropping and tillage are still scarce. Prior studies either only identified responsive taxa in the samples from CC treatments that showed significant differences in ordination methods [30] or searched for microbes with specific genes, such as those related to residue decomposition [36]. No CC metagenomics study has sought indicator taxa at lower taxonomic ranks without any such constraining conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms also respond quickly to changes in soil environment conditions, due to their high surface to volume ratio, which can provide an early signal in soil improvement or degradation, thus has been recommend as a key indicator of soil health(Nielsen et al ., 2002). However, the effect of tillage practices on soil microbial communities are complex and diverse(Helgason et al ., 2010; Sun et al ., 2018; Li et al ., 2020; Rincon-Florez et al ., 2020) and most studies by now mainly focused on farmland topsoil or soils within 1-m depth(Hartman et al ., 2018; Nevins et al ., 2018; Alahmad et al ., 2019), and soil below 1 meter, which contains more carbon than the topsoil(Jobbágy and Jackson, 2000) and belongs to Earth’s Critical zone, was often overlooked. However, microbes inhabiting in the deep soils (> 1 m) may substantially impact long-term carbon sequestration, mineral weathering and crop production(Eilers et al ., 2012; Sagova-Mareckova et al ., 2016; Pries et al ., 2017), and play important roles in bridging aboveground vegetation with parent soils and even acts as an essential buffer protecting underground water(Chorover et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%